The role of supplier relationship strategies, relationship with customer, and information sharing on firm performance - Jahid, Md. Abu; Sukardi, Sukardi; Purwoko, Purwoko; Pasiri, Rafi Al (Universitas Ahmad Dahlan, 2023)
Purpose-This study examines the correlation between supplier relationship strategies, relationship with customer, and information sharing on firm performance. Design/Methodology/Approach-The study population consisted of employees of Bank in Asia. The data of this study was collected through questionnaires, and the study sample consisted of 100 respondents. Outer model and inner model analysis techniques were applied to this research data using an analysis application called Smart PLS version 3.0. Findings-The results showed that supplier relationship strategies and information sharing have a positive effect on firm performance. Then, the opposite results are shown by relationship with customer and firm performance which shows a negative influence. Research limitations/implications-Banking businesses need to improve or optimize supplier relationship strategies, relationship with customers, and information sharing to drive firm performance growth. In this study, it is necessary to emphasize or improve relationships with customers to improve firm performance, because this study actually shows a negative influence. Originality/value-Studies on the performance of companies in the banking business, especially Bank in Asia can still be said to be quite limited. Previous research has not discussed supplier relationship strategies, relationship with customers, and information sharing to analyze company performance in the banking business.